2019
DOI: 10.1021/acs.joc.9b00782
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed Asymmetric α-Thiocyanation of Oxindoles: Synthesis of Chiral Tertiary 3-Thiocyanatoxindoles

Abstract: An enantioselective thiocyanation of oxindoles has been developed for the first time using a bifunctional cinchona-derived organo-catalyst and N-thiocyanatophthalimide as the electrophilic thiocyanation source in the presence of 2-naphthol as the additive. Various enantioenriched 3,3′-disubstituted oxindoles with SCN-containing quaternary carbon stereocenters were synthesized under mild conditions in high yields (up to 99%) and good enantioselectivities (up to 6:94 er).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 46 publications
(23 reference statements)
1
28
0
Order By: Relevance
“…reported an asymmetric α‐ thiocyanation with the help of a chiral Evans auxiliary group [14] . Recently, our group successively developed a catalytic asymmetric electrophilic thiocyanation of β‐ ketoesters and oxindoles (Scheme 1B) [11d,15] . Based on our research interest in the field of cyano‐containing chemicals, [16] we disclosed the asymmetric tandem oxa‐Michael addition and electrophilic thiocyanation to produce functionalized flavanones in one‐pot step.…”
Section: Methodsmentioning
confidence: 99%
“…reported an asymmetric α‐ thiocyanation with the help of a chiral Evans auxiliary group [14] . Recently, our group successively developed a catalytic asymmetric electrophilic thiocyanation of β‐ ketoesters and oxindoles (Scheme 1B) [11d,15] . Based on our research interest in the field of cyano‐containing chemicals, [16] we disclosed the asymmetric tandem oxa‐Michael addition and electrophilic thiocyanation to produce functionalized flavanones in one‐pot step.…”
Section: Methodsmentioning
confidence: 99%
“…One year later,t he same group reported an extension of their methodology to the a-thiocyanation of 3-substituted oxindoles 26 (Scheme 12). [20] Indeed, by using as imilar catalytic system and the 2-naphthol as ac o-catalyst, the expected thiocyanatedp roducts 27 were afforded in excellent yields (e.r.u p to 94:6). Note that the stereoselectivity outcome of the reaction was substrate-dependent.…”
Section: N-thiocyanatosuccinimide and N-thiocyanato-phthalimide Reagentsmentioning
confidence: 97%
“…Recently, this research area has attracted increasing attention and several remarkable works have been reported [3] . Chen and coworkers developed a new reagent thiocyanatosaccharin (NTSc) and reported catalytic asymmetric α‐thiocyanations of cyclic β‐ketoesters and oxindoles, recently [3a–c] . In 2019, we designed and synthesized an electrophilic N‐thiocyanodibenzenesulfonimide (NTSI) reagent, which has been applied for thiocyano oxyfunctionalizations of alkenes and thiocyano semipinacol rearrangement of allylic alcohols [3d–e] .…”
Section: Introductionmentioning
confidence: 99%